Predicting admission to post-acute inpatient rehabilitation in patients with acute stroke - Feng-Hang Chang; Yen-Nung Lin; Tsan-Hon Liou; Jui-Chi Lin; Cheng-Hsun Yang; Hsien-Lin Cheng (Medical Journals Sweden, 2020)
Objective: To identify predictors of admission to post-acute inpatient rehabilitation settings follow-ing acute care for stroke survivors in Taiwan. Design: Prospective observation study. Participants: Stroke survivors (n = 558) admitted to acute care wards for inpatient rehabilitation (62% male; mean age 60.0 ± 12.2 years). Methods: The primary outcome was whether survivors were admitted to post-acute inpatient rehabilitation settings after discharge from acute care wards. Logistic regression model was adopted to examine the predictors of admission to post-acute inpatient rehabilitation. A receiver operating characteristic curve was drawn to compute the ability of the predictors to discriminate the outcome. Results: Multivariate analysis results indicated Activity Measure Post-Acute Care "6-Clicks" Basic Mobility score to be the only significant predictor of admission to post-acute inpatient rehabilitation (odds ratio = 0.44, 95% confidence interval: 0.34-0.56). Receiver operating characteristic curve analysis results indicated that the cut-off point for Basic Mobility was 13 (standardized score: 33.99). This yielded a sensitivity value of 0.98 and a specificity value of 0.96 for determining the admission to post-acute inpatient rehabilitation. Conclusion: Activity Measure Post-Acute Care "6-Clicks" Basic Mobility subscale scores at admission for acute care can predict admission to post-acute inpatient rehabilitation for stroke survivors in Taiwan. This tool can aid clinicians in formulating adequate discharge plans at an early stage, and thus improve the quality of care.